Republic of Congo : Enhanced Heavily Indebted Poor Countries Initiative; Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses Congo's progress under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). In the view of the staff of IDA and the IMF, Congo has met in full all of the triggers for reaching the completion point. All key decisions, actions, and measures required to observe the triggers have been taken, including a satisfactory track record of implementation for public investment management, procurement, governance and anticorruption, improvement in the internal controls and accounting of the state-owned oil company, and oil commercialization.